A case of neurinoma originating in the inferior alveolar nerve - YATA, Hiroaki; KINOSHITA, Yasuo; SUZUKI, Masayuki; YAJIMA, Tetsuya (Japanese Journal of Oral and Maxillofacial Surgery, 2001)
Neurinoma is a benign tumor arising from Schwann cells. In the oral and maxillofacial region, tumors usually arise in the tongue and rarely occur in the mandible. We present a case of neurinoma originating in the inferior alveolar nerve. A 39-year-old man was referred to our hospital because of discomfort in the right side of the mandible. The clinical diagnosis was a mandiblar tumor. The tumor was extirpated with the inferior alveolar nerve. The histopathological diagnosis was neurinoma. The tumor was confirmed to have originated in the inferior alveolar nerve.